Transcriptomic and epigenomic profiling reveals altered responses to diesel emissions in Alzheimer's disease both in vitro and in population-based data - Saveleva, Liudmila; Cervena, Tereza; Mengoni, Claudia; Sima, Michal; Krejcik, Zdenek; Vrbova, Kristyna; Sikorova, Jitka; Mussalo, Laura; de Crom, Tosca O E; Šímová, Zuzana; Ivanova, Mariia; Shahbaz, Muhammad Ali; et al. (Alzheimer's & dementia, 2024)
INTRODUCTION: Studies have correlated living close to major roads with Alzheimer's disease (AD) risk. However, the mechanisms responsible for this link remain unclear. METHODS: We exposed olfactory mucosa (OM) cells of healthy individuals and AD patients to diesel emissions (DE). Cytotoxicity of exposure was assessed, mRNA, miRNA expression, and DNA methylation analyses were performed. The discovered altered pathways were validated using data from the human population-based Rotterdam Study. RESULTS: DE exposure resulted in an almost four-fold higher response in AD OM cells, indicating increased susceptibility to DE effects. Methylation analysis detected different DNA methylation patterns, revealing new exposure targets. Findings were validated by analyzing data from the Rotterdam Study cohort and demonstrated a key role of nuclear factor erythroid 2-related factor 2 signaling in responses to air pollutants. DISCUSSION: This study identifies air pollution exposure biomarkers and pinpoints key pathways activated by exposure. The data suggest that AD individuals may face heightened risks due to impaired cellular defenses. HIGHLIGHTS: Healthy and AD olfactory cells respond differently to DE exposure. AD cells are highly susceptible to DE exposure. The NRF2 oxidative stress response is highly activated upon air pollution exposure. DE-exposed AD cells activate the unfolded protein response pathway. Key findings are also confirmed in a population-based study.
Keywords: Male; NF-E2-Related Factor 2; lidé středního věku; metylace DNA; next‐generation sequencing (NGS); Vehicle Emissions; stanovení celkové genové exprese; Humans; Middle Aged; senioři; látky znečišťující vzduch; mužské pohlaví; Female; epigenomika; faktor 2 související s NF-E2; MicroRNAs; Aged; air–liquid interface (ALI); traffic emissions; ženské pohlaví; air pollution; nuclear factor erythroid 2–related factor 2 (NRF2); DNA Methylation; Alzheimerova nemoc; Air Pollutants; Epigenomics; Alzheimer's disease (AD); Olfactory Mucosa; Transcriptome; Gene Expression Profiling; transkriptom; mikro RNA; čichová sliznice; Alzheimer Disease; výfukové emise vozidel; heat shock protein (HSP); lidé; traffic‐related air pollution (TRAP) olfactory mucosa (OM)